Penerapan Aplikasi Penjualan E-Sembako Berbasis Android Pada Toko Rafa Untuk Meningkatkan Omset Pendapatan - Istikomah Indah Lestari; Aris Sudianto; Muhamad Sadali; Hamzan Ahmadi (Infotek: Jurnal Informatika dan Teknologi, 2022)
The rise of based business activities electronic certainly has a big impact on people's lives, especially the trade sector as experienced by Rafa store, especially at this time the world is being hit by a disaster, namely the COVID-19 pandemic which requires people to stay at home and limit activities outside the home. This is the backgroundof the author to create an application that can facilitate the community, especially housewives in meeting their household needs. This study aims to find out how the effectiveness of based applications electronic in increasing revenue at Rafa sawing stores. The method used in this study is to make direct observations to the rafa shop and conduct interviews with shop owners. By observing the researchers can find out the condition of the store both in terms of product availability and in terms of service By conducting interviews, researchers can find out the ins and outs of the store in terms of finances, availability of goods and service conditions applied by Rafa Stores at this time. For this reason, researchers are determined to apply the concept electronic to this Rafa store by building sales system E-grocery an Android based at the Rafa Sawing store.